Consensus Guidelines on Rodent Models of Restless Legs Syndrome. Issue 3 (31st December 2020) - Salminen, Aaro V.; Silvani, Alessandro; Allen, Richard P.; Clemens, Stefan; Garcia‐Borreguero, Diego; Ghorayeb, Imad; Ferré, Sergi; Li, Yuqing; Ondo, William; Picchietti, Daniel L.; Rye, David; Siegel, Jerome M.; et al.
ABSTRACT: Restless legs syndrome (RLS) is a chronic sensorimotor disorder diagnosed by clinical symptoms. It is challenging to translate the diagnostic self‐reported features of RLS to animals. To help researchers design their experiments, a task force was convened to develop consensus guidelines for experimental readouts in RLS animal models. The RLS clinical diagnostic criteria were used as a starting point. After soliciting additional important clinical features of RLS, a consensus set of methods and outcome measures intent on capturing these features—in the absence of a face‐to‐face interview—was generated and subsequently prioritized by the task force. These were, in turn, translated into corresponding methods and outcome measures for research on laboratory rats and mice and used to generate the final recommendations. The task force recommended activity monitoring and polysomnography as principal tools in assessing RLS‐like behavior in rodents. Data derived from these methods were determined to be the preferred surrogate measures for the urge to move, the principal defining feature of RLS. The same tools may be used to objectively demonstrate sleep‐state features highly associated with RLS, such as sleep disturbance and number and periodicity of limb movements. Pharmacological challenges and dietary or other manipulations that affect iron availability are desirable to aggravate or improve RLS‐like behavior and lend greater confidence that the animal model being proffered replicates key clinical features of RLS. These guidelines provide the first consensus experimental framework for researchers to use when developing new rodent models of RLS. © 2020 International Parkinson and Movement Disorder Society